Letter : Spain - Stolz, George
029-0165-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe IFTU St/H TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter: F.I. de Sol No. 499 23rd April, 1937. Mr. Walter M. Citrine, LONDON Dear Comrade Citrine SPAIN With reference to your request that Comrade Jouhaux should make representations to the Prime Minister regarding protection of shipping, I have now heard from Jouhaux that he took the action required, and that "the Prime Minister has assured us that he will give the greatest attention to his problem in order to find a rapid solution". Yours sincerely, G. Stolz, Assistant Secretary: 292/946/29/165